Risk factors associated with osteoporosis and fracture in psoriatic arthritis. Issue 21 (5th November 2021) - Wang, Yu; Song, Zhi-Bo; Deng, Xue-Rong; Zhang, Xiao-Hui; Zhang, Zhuo-Li
Abstract: Background: Although there are few studies mentioned there may be some relationship between psoriatic arthritis (PsA) and osteoporosis, clinical data in real world still need to be clarified in China. The aim of this study was to assess the areal and volumetric bone mineral density (BMD), frequency of fracture, and risk factors in patients with PsA. Methods: A total of one hundred PsA patients who visited Peking University First Hospital and one hundred age- and sex-matched healthy controls with DXA data were enrolled in the study. Patients with clinical fractures confirmed by X-ray during follow-up were also recorded. Clinical characteristics of the patients were recorded and compared between the abnormal BMD group and the normal BMD group, as well as between the fracture and non-fracture groups. Risk factors for fracture and low BMD were analyzed. Results: Mean BMD at the total hip and femoral neck was significantly lower in PsA patients than that in healthy controls (0.809 ± 0.193 vs. 0.901 ± 0.152 g/cm 2, P   =  0.041; 0.780 ± 0.146 vs. 0.865 ± 0.166 g/cm 2, P   =  0.037, respectively). Moreover, lumbar spine BMD was negatively correlated with psoriasis duration, swollen joint count and DAS28-CRP ( r  = –0.503, –0.580, –0.438; P  < 0.05). Total hip BMD and femoral neck BMD were negatively correlated with HAQ ( r  = –0.521, –0.335; P  < 0.05). Fractures occurred in 29 patients during the follow-up period. Logistic regression analysis showed that older age (OR 1.132 [95%CI: 1.026–1.248), P  < 0.05], higher HAQ score (OR 1.493, 95%CI: 1.214–1.836, P  < 0.01), higher disease activity index for psoriatic arthritis (OR 1.033, 95% CI: 1.002–1.679, P  < 0.05) and hip joint involvement (OR 6.401, 95% CI: 4.012–44.180, P  < 0.05) were risk factors for fracture in the multivariate model. Conclusions: Increased risks of osteoporosis and fracture were found in PsA patients compared to healthy controls. Besides age, high disease activity and hip joint involvement were risk factors for decreased BMD and fracture.